Economic security of the enterprise: The essence, structure and mechanism of ensuring - Liubov Kovalska; Оleksandr Holii; Valentyn Holii (Економічний форум)
The article conducts theoretical studies of the essence of economic security of the enterprise. The following characteristics of economic security of the enterprise are highlighted: protection from the negative impact of factors, security of economic development and stability, the state of efficient use of resources, the ability to prevent the negative impact of environmental factors. It is proposed to consider the economic security of the enterprise as the ability of the socio-economic system to resist and create protection from destabilizing factors of internal and external environment, while ensuring the sustainability of economic development through the effective use of available and potential resources. The prerequisites (efficient and rational use of all available and potential resources; rapid response to changes in economic, political, social, market, geopolitical, international and other factors of influence; availability of preventive mechanisms for protection and prevention of negative impact of factors) and Consequences (Ensuring the economic development of the enterprise in time dimension; ensuring the sustainability of the socio-economic system of the enterprise) ensuring the economic security of the enterprise. The structure of economic security of the enterprise is considered. It is proposed to include the following elements: financial, intellectual and personnel, information, technical and technological security. A mechanism for ensuring the economic security of the enterprise has been developed. The proposed mechanism contains the following elements: the subject and object of ensuring the economic security of the enterprise; principles of ensuring the economic security of the enterprise; functions of ensuring the economic security of the enterprise; directions for ensuring the economic security of the enterprise; methods for ensuring the economic security of the enterprise; tools for ensuring the economic security of the enterprise. The choice of a strategy for ensuring economic security of an enterprise is justified: a strategy for forming prerequisites for ensuring economic security (state of danger); strategy for focusing on ensuring economic security (state of risk); strategy for activating processes to ensure economic security (state of threat); strategy for maintaining the state of economic security (state of security)